Development of Teaching Modules Based on Panai Malay Ethnomathematics to Improve Students' Critical Thinking Skills - Tanjung, Ummi Amalia Putri; Pasaribu, Endi Zunaedy; Lestari, Rizki (Journal of English Language and Education, 2025)
This study aims to determine “how the development of teaching modules based on Panai Malay ethnomathematics can improve students' critical thinking skills.” This study is a development study using the ADDIE development model. The subjects of this study were 11th grade students at Madrasah Aliyah Swasta al Washliyah Marbau. Data was collected using tests. The development of ethnomathematics-based teaching modules to enhance students' critical thinking skills is the problem addressed in this study. This study aims to test students' critical thinking skills in solving problems in learning the system of two-variable equations and to obtain results from normality tests, homogeneity tests, and hypothesis tests that influence teaching critical thinking skills to students at the Al Washliyah Marbau Private Madrasah Aliyah in North Labuhanbatu Regency.